Geochronology and Paleoenvironmental Changes of Late Pleistocene Sediments in the Ross Sea, Antarctica - Li, Guogang; Bu, Ruyuan; Yi, Liang; Hu, Bangqi; Li, Yunhai; Ji, Youjun; Li, Yixin; Wang, Liang (Frontiers in Earth Science, 2022)
Palaeoceanographic studies are largely limited by poor carbonate preservation in high-latitude regions. To improve our knowledge in this key area, we studied a sediment core (ANT32-RA05C) in terms of paleomagnetic and 230Th dating and geochemical properties, collecting from the continental slope of the Ross Sea, Antarctica. The two major results are as follows: (1) the sedimentation rate based on 230Th isotopes is 1.37 cm/kyr, agreeing well with the correlation of the relative paleomagnetic intensity of core ANT32-RA05C to changes in Earth’s magnetic intensity; and (2) the sediments contain ice-rafted debris (IRD) over 30%, with a considerable contribution of siliceous deposits. Integrating geochronological and geochemical properties of the studied core, a correlation of regional paleoenvironmental process to the EPICA Dome C (EDC) Antarctic temperature is established, inferring that IRD input and primary productivity are both enhanced in a warm climate. Moreover, a leading phase of biogenic processes to changes in ice sheet in the Ross Ice Shelf is observed, highlighting a dominant role of oceanic circulation in ice-sheet retreat during the last deglaciation. Overall, the sedimentary record in the Ross Sea documents some key features of paleoenvironmental processes in the late Pleistocene, which could be correlated to large-scale changes in the Antarctica and thus worth of further investigation in future.